2019
DOI: 10.3348/kjr.2018.0174
|View full text |Cite
|
Sign up to set email alerts
|

Fat Quantification in the Vertebral Body: Comparison of Modified Dixon Technique with Single-Voxel Magnetic Resonance Spectroscopy

Abstract: ObjectiveTo compare the lumbar vertebral bone marrow fat-signal fractions obtained from six-echo modified Dixon sequence (6-echo m-Dixon) with those from single-voxel magnetic resonance spectroscopy (MRS) in patients with low back pain.Materials and MethodsVertebral bone marrow fat-signal fractions were quantified by 6-echo m-Dixon (repetition time [TR] = 7.2 ms, echo time (TE) = 1.21 ms, echo spacing = 1.1 ms, total imaging time = 50 seconds) and single-voxel MRS measurements in 25 targets (23 normal bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
11
2
3
Order By: Relevance
“…In water-fat imaging, multiple echoes in a gradient echo acquisition are used to create a time-dependent phase shift between water and fat MR signals ( 9 ). Strong correlations have been shown between bone marrow fat fractions in lumbar vertebral bodies obtained from modified Dixon sequences and those obtained from single-voxel magnetic resonance spectroscopy (MRS), which is considered a gold standard method for quantification of bone marrow fat ( 10 , 11 ). The iterative decomposition of water and fat with echo asymmetry and least-squares estimation (IDEAL) technique has also been developed through further modifications of the Dixon technique to overcome field inhomogeneities during water-fat separation with maximal signal-to-noise ratio (SNR) and minimal scanning time ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In water-fat imaging, multiple echoes in a gradient echo acquisition are used to create a time-dependent phase shift between water and fat MR signals ( 9 ). Strong correlations have been shown between bone marrow fat fractions in lumbar vertebral bodies obtained from modified Dixon sequences and those obtained from single-voxel magnetic resonance spectroscopy (MRS), which is considered a gold standard method for quantification of bone marrow fat ( 10 , 11 ). The iterative decomposition of water and fat with echo asymmetry and least-squares estimation (IDEAL) technique has also been developed through further modifications of the Dixon technique to overcome field inhomogeneities during water-fat separation with maximal signal-to-noise ratio (SNR) and minimal scanning time ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…While MRI‐determined PDFF has been proven as a reliable noninvasive quantitative imaging biomarker (QIB) for the assessment of liver steatosis, its impact on bone marrow fat quantification is a significant, yet not so well‐explored issue. Owing to the distinct microarchitectural characteristics of the bone, it is important to validate the precision of MRI‐determined PDFF for bone marrow fat quantification for several reasons: first, bone marrow adipose tissue is not homogeneously distributed within the trabecular bone matrix and can exhibit a wider range of fat content than most visceral organs, ranging from 0–80% . Second, susceptibility differences at the interface between bone marrow and trabecular bone induce a rapid decay of the measured gradient echo signal with increasing echo time and can confound PDFF estimation, especially at high field strengths .…”
mentioning
confidence: 99%
“…Owing to the distinct microarchitectural characteristics of the bone, it is important to validate the precision of MRI-determined PDFF for bone marrow fat quantification for several reasons: first, bone marrow adipose tissue is not homogeneously distributed within the trabecular bone matrix and can exhibit a wider range of fat content than most visceral organs, ranging from 0-80%. 12 Second, susceptibility differences at the interface between bone marrow and trabecular bone induce a rapid decay of the measured gradient echo signal with increasing echo time and can confound PDFF estimation, especially at high field strengths. 13,14 The first validation studies have shown high accuracy for MRI-determined PDFF using the chemically determined fat content in ex vivo water-fat trabecular bone phantoms 15,16 and single-voxel 1 H-MR spectroscopy (MRS)-based fat fraction estimations of spine marrow 14 as the reference standard.…”
mentioning
confidence: 99%
“…Основным результатом следует признать обнаруженную обратную корреляцию (r = -0,55, p = 0,0004) между СЖ и МПКТ, которая свидетельствует о том, что процессы снижения МПКТ и увеличения содержания жира в здоровых позвонках протекают одновременно. Аналогичная достоверная корреляция между этими расчетными параметрами, измеренными в телах поясничных позвонков, была найдена для испытуемых среднего и пожилого возраста [11,12]. В работе [12] исследовалась группа волонтеров, средний возраст которых составлял 49,1 ± 19,0 года.…”
Section: Discussionunclassified